2013
DOI: 10.4269/ajtmh.12-0643
|View full text |Cite
|
Sign up to set email alerts
|

Sociocultural Determinants of Anticipated Vaccine Acceptance for Acute Watery Diarrhea in Early Childhood in Katanga Province, Democratic Republic of Congo

Abstract: Abstract. Rotavirus and oral cholera vaccines have the potential to reduce diarrhea-related child mortality in low-income settings and are recommended by the World Health Organization. Uptake of vaccination depends on community support, and is based on local priorities. This study investigates local perceptions of acute watery diarrhea in childhood and anticipated vaccine acceptance in two sites in the Democratic Republic of Congo. In 2010, 360 randomly selected non-affected adults were interviewed by using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Several other cross-sectional evaluations conducted at single time points in endemic and epidemic cholera settings have similarly documented varying WaSH KAPs [2426]. The improvements we observed at first follow-up survey after the OCV campaign were similar to that of a KAP evaluation in Haiti conducted before and 3 months after an OCV campaign in 2012, the only other pre- and post-campaign KAP evaluation [27].…”
Section: Discussionsupporting
confidence: 77%
“…Several other cross-sectional evaluations conducted at single time points in endemic and epidemic cholera settings have similarly documented varying WaSH KAPs [2426]. The improvements we observed at first follow-up survey after the OCV campaign were similar to that of a KAP evaluation in Haiti conducted before and 3 months after an OCV campaign in 2012, the only other pre- and post-campaign KAP evaluation [27].…”
Section: Discussionsupporting
confidence: 77%
“…Both RV and NoV are prone to gene recombination, resulting in new variants or genotypes. Therefore, the investigation of genotypic distribution is of great significance for epidemiological studies of viruses and the development and application of vaccines [24,25]. The prevailing RV serotypes and genotypes worldwide are G1P8, G2P4, G3P8, and G4P8 [24].…”
Section: Discussionmentioning
confidence: 99%
“…While vaccines in many countries are provided free-of-charge to facilities, most providers request a payment for a vaccination card to cover administrative and workforce costs for immunization services and monitoring during the infant's first year of life. 49 Removing monetary barriers through small cash incentives or reducing user fees for immunization can improve uptake in the short-term, 49,50 though it may not be a sustainable long-term option. A study in the Democratic Republic of the Congo demonstrated that uptake of the rotavirus vaccine was 99% if the vaccine was provided free of charge.…”
Section: Cost Burdenmentioning
confidence: 99%